(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The various types of programs require the trust of each program to authorize or determine the identity of the person seeking its services. The purpose of this program is to ensure that the services provided are only available to the user personally and not to anyone else. If there are no solid personal recognition schemes, these programs are at risk of being deceived by a fraudster. ATMs have suffered a lot in recent years due to PIN theft and other ATM frauds due to authentication (PIN) mode. In this paper, we have proposed a multifactor certificate (PIN and Fingerprint) that strengthens the safety and security of ATMs and their users. The proposed plan shows the formation of three levels. The first phase is the verification phase, which focuses on the registration phase, the development phase, the removal of features and fingerprint matching. The second stage is the end of the data that serves as a repository for all ATM users registered as indicators and PIN as text. The final section describes the platform for discussing banking transactions such as balance questions, small statements and withdrawals. Microsoft windows 8 has been used as a startup application platform, with advanced C # programming language and 2010 SQL server as a backend. The application test was based on the False Rejection Rate (FAR), False Acceptance Rate (FAR), Medium Term Matching (AMT) and Total Error Rate (TER) performed, indicating the safety and reliability of the verification and authentication system of the proposed ATM user